Formation of Sociocultural Competence of University Students by Means of A Foreign Language - O L Shabalina; A A Novosyolova (Peoples' Friendship University of Russia (RUDN University), 2012)
The article is devoted to the formation of sociocultural competence in the process of learning a foreign language by university students as part of their preparedness for intercultural communication in the socio-cultural activities.